Sinusite aguda em crianças: estudo retrospectivo de complicações orbitárias - Mekhitarian Neto, Levon (2007)
Among the complications of sinusitis, those that involve the orbital region are the most frequent. AIM: the objective of this paper is to show an incidence of orbital cellulites (OC) secondary to acute sinusitis in children. Study design: retrospective. METHODS: After board approval, the charts of all pediatric patients diagnosed with orbital complications secondary to sinusitis, seen at the Pediatric and at the ENT clinics of the HPEV, between 1985 and 2004, were evaluated. The data was analyzed considering gender, age, clinical presentation, period of hospitalization, image study, and treatment. RESULTS: from 1985 to 2004, 25 patients were diagnosed with OC secondary to sinusitis, presenting an incidence of 6% . Males predominated, the median age was 6.5 years, and the maxillary was the most frequently involved sinus. Twenty-four patients presented mild peri-orbital swallowing. All 25 patients presented X-Ray alterations. One patient with proptosis had a subperiosteal abcess seen on the CT-scan. The average time of hospitalization was 4 days. All 25 patients received IV antibiotics, 2 required surgery. CONCLUSION: The incidence of orbital complications secondary to sinusitis is low, and although the majority of cases are early diagnosed and respond well to medication treatment, a surgical intervention may be required.